Species identification of Coagulase Negative Staphylococci (CoNS) isolates in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) - Nurul Azirah Mohamad Sani,; Hassriana Fazilla Sapri,; Ainihayati Noordin,; Neoh, Hui-min; Salasawati Hussin, (UKM Medical Molecular biology Institute, UMBI, 2011)
Coagulase negative Staphylococcus (CoNS) are common colonizers of the human skin but has become increasingly recognized as agents of clinically significant infections. At the Universiti Kebangsaan Malaysia Medical Centre (UKMMC), the prevalence of CoNS among staphylococcus genus in 2009 was 47.1%. The aim of this study was to identify Staphylococcus epidermidis, S. saprophyticus and S. xylosus from the CoNS and MRCoNS (methicillin resistant CoNS) collected in 2009 using a multiplex PCR approach with primers specific for each species. Our results showed that S. epidermidis is the most common species among both MRCoNS and CoNS isolates in UKMMC. Among 1142 CoNS strains, 68.4% were S. epidermidis, 1.3% were S. saprophyticus while 30.3% were non-typeable (other species). A total of 659 CoNS strains have been identified as methicillin resistant (MRCoNS); where 68.1% were S. epidermidis,1.5% was S. saprophyticus and 30.3% were from other CoNS species. S. xylosus was not identified among the isolates.